STAR (SEE, THINK, ACCURATE, RESPONSIBLE) CAREER INTERVENTION FOR STUDENT-ATHLETES CAREER ENGAGEMENT - Hasna Hafizhah Salma; Puji Lestari Suharso (JIP (Jurnal Intervensi Psikologi), 2023)
ABSTRACT: Student-athletes are faced with two possible carrier choices either to remain athletes in the long term or to choose an alternative path. When they are not engaged in their choice, this may lead to indecision in the future. Furthermore, a need analysis conducted at Vocational High School X showed that student-athletes are not involved in their carrier, hence, they need intervention as external support. Therefore, this study aimed to examine the effectiveness of STAR career intervention in increasing student-athletes career engagement, enabling appropriate choices. This was a quasi-experiment with a one-group-pretest-posttest design, and the subjects were 9 student-athletes. The results analyzed using the Wilcoxon test showed that STAR career intervention significantly increased understanding of the material (p-value=0.012), career engagement (p-value=0.002), and reaction evaluation (p-value=0.018). The implications of this study can be applied by school guidance counselors.